Pedalling technique and postural stability during incremental cycling exercise . Relationship with cyclist FMSTM score - Rannama, I.; Pedak, K.; Reinpold, K.; Port, K. (LASE Journal of Sport Science, 2016)
Purpose of the present study was to examine the changes in the pedalling kinetics and in the ground reaction forces as a measure of the cycling stability during an incremental cycling exercise. Furthermore, we compared the effectiveness of the pedalling technique and postural stability between the high and low Functional Movement Screen score (FMSTM) cyclists and analysed the relationships between the cycling specific postural stability, pedalling kinetics and cyclists FMSTM test scores. 31 competitive cyclists (18.5 +/- 2.1y; 1.81 +/- 0.06m; 73.7 +/- 7.5kg) were categorized based on the (FMSTM) test results in a low (LS, n=19; FMS.14) and a high (HS, n=12; FMS>14) score group. The pedalling effectiveness and absolute symmetry indexes, as well the ground reaction force (GRF) were measured during incremental cycling exercise. Cycling specific postural stability was expressed as the body mass corrected standard deviation of 3 linear and 3 angular GRF components during a 30sec cycling at four power levels. We found that during incremental cycling exercise the pedalling effectiveness, smoothness and cyclist's swaying in all three planes increased according to the combined effect of the workload and fatigue. Cyclists with high FMSTM score showed a lower bilateral pedalling asymmetry and a greater cycling specific postural stability, but showed no differences in the pedalling effectiveness and smoothness compared with the LS cyclists. Cyclist's FMSTM score were moderately related with the stability components acting along the horizontal plane. The pedalling effectiveness, smoothness and bilateral asymmetry were inversely related to the components acting perpendicularly to the horizontal plane.